Ultrasonographic measurements of the inferior vena cava diameter in newborns: is it a useful tool for choosing an umbilical venous catheter? - Galdo, Francesca; Trappan, Antonella; Cossovel, Francesca; Rodriguez-Perez, Carmen; Ronfani, Luca; Montaldo, Paolo; Bibalo, Cristina; Travan, Laura; Risso, Francesco Maria (Frontiers in Pediatrics, 2023)
Objectives The primary outcomes of this study were to evaluate the diameters of the inferior vena cava (IVC) in a cohort of newborns and the correlation between newborn weight and IVC diameter. The secondary outcome was to evaluate the concordance between the measurements performed by the two investigators. Methods Two blind examiners performed an ultrasonographic (US) evaluation of the IVC diameter in neonates with a weight ranging from 2 to 4 kg. The exclusion criteria included hemodynamic instability, known vascular malformations, and major congenital malformations. Results A total of 143 neonates were enrolled between June 2019 and January 2021. All the US examinations were performed in the first 3 days of life. After dividing the patients into two groups according to their weight at the time of examination (2.0–2.99 kg and 3.0–4.0 kg), the median IVC diameters measured by examiner 1 were 3.1 mm (interquartile range 2.8–3.4) and 3.4 mm (interquartile range 2.9–3.8) (p = 0.003) for the two groups, respectively. The median IVC diameters measured by examiner 2 were 3.1 mm (interquartile range 2.6–3.3) and 3.3 mm (interquartile range 2.8–3.8) (p = 0.004) for the two groups, respectively. The intraclass correlation coefficient was 0.93 (95% CI: 0.90–0.95). Conclusion The IVC diameter values varied widely from 1.2 to 5.2 mm in newborns weighing 2–4 kg, and a low correlation between newborn weight and IVC diameter was found, so measuring IVC diameter may be a recommended step prior to inserting a umbilical venous catheter (UVC). The concordance between operators was good. We contemplated that the IVC diameter could be a potentially useful tool to identify the most appropriate UVC, thus reducing the risk of catheter-related thrombosis.